The agriculture-nutrition nexus in Haiti - Nachigera Mushagalusa, Gustave; Karume, Katcho; Vwima, Stany; Francis, Judith Ann (Technical Centre for Agricultural and Rural Cooperation, 2017)
More than one-third of Haiti’s population remains food insecure, despite the efforts of international donors, government ministries and numerous non-governmental organisations (NGOs). Enough food is available in the country to feed everyone, but half of it is imported every year. Chronic poverty prevents much of the country’s population from accessing the food they need. This Technical Brief gives key recommendations to improve food and nutrition security in Haiti.